Enhancement of SiO2/Si(001) interfacial oxidation induced by thermal strain during rapid thermal oxidation - Ogawa, Shuichi; Tang, Jiayi; Yoshigoe, Akitaka; Ishidzuka, Shinji; Takakuwa, Yuji (The Journal of chemical physics, 2016)
Rapid thermal oxidation, in which samples are intensely heated to a preset temperature, is used to grow silicon oxide on Si substrates while avoiding significant diffusion of impurities into the substrate. In previously proposed reaction models for rapid thermal oxidation, the oxidation rate is only determined by the temperature and O2 pressure. Therefore, it is believed that the rate of oxidation at a preset temperature is independent of the initial substrate temperature. In this study, the interfacial oxidation reactions that follow Si(001) surface oxidation were observed using real-time Auger electron spectroscopy. Interfacial oxidation was enhanced when the substrate temperature was increased from temperature T 1 to temperature T 2 at the end of Si(001) surface oxidation. As a result, strong T 1 and T 2 dependences of the interfacial oxidation rate were observed. The interfacial oxidation rate at T 1 = room temperature was more than 10 times higher than that at T 1 = 561 °C, even for the same T 2 (682 °C). Additionally, the activation energy of interfacial oxidation was 0.27 eV, and independent of T 1. This activation energy corresponds to the “no elementary step” proposed as the rate-limiting reaction in previous studies. These results can be explained using the unified Si oxidation reaction model mediated by point defect generation: high magnitude thermal strain is generated when the difference between T 2 and T 1 is large, and this strain generates point defects that become reaction sites for interfacial oxidation.